Managing Clinical Trials Amid Healthcare Policy Reforms: Challenges and Opportunities: Managing Clinical Trials and Healthcare Policy Reforms - Hayat, Babar; Mumtaz, Naheed; Choudry, Sadia; Khan, Muhammad Ayub; Butt, Amna Iqbal; Chaudry, Zahid Azam; Hussain, Muhammad (Pakistan Journal of Health Sciences, 2024)
Clinical trial management is becoming more influenced by policies in healthcare reform, especially if those reforms are actively affecting regulations, access to healthcare, and compliance. Objectives: To find out the implications of healthcare reforms for the administration, supervision and outcomes of the clinical trials. Methods: This study was carried out according to the PRISMA guidelines. Eight scholarly databases of peer-reviewed research articles were used including PubMed, ScienceDirect, and Google Scholar. For this review, articles published from January 2016 to April 2024 were collected. This paper reviewed articles centred on the impact of healthcare reform policies on clinical trials, especially in chronic diseases and novel therapies in North America, Europe, and Asia. Through screening, 96 articles were taken for initial screening. 16 articles were fully reviewed based on challenges and prospects of clinical trial management in the course of changes in healthcare system reforms. Results: Healthcare policy reforms face obstacles like regulatory challenges, added bureaucracy, and highly volatile patient care accessibility. But there are also some benefits like optimized approval of trials-based procedures, better patient engagement, and increased trial effectiveness. Conclusions: It was concluded that clinical research can be more effective and scalable if proactive adaptive strategies are integrated and trial protocols are aligned with evolving policy changes. Adapting proven trial management practices in healthcare settings has the potential to enhance patient outcomes and promote operational efficiency in clinical research around the world.